Multisensory learning and reading skills in second grade general basic education students at Unidad Educativa Particular Bilingüe Santo Domingo de Guzmán, school year 2019-2020 - Abad Rojas, Briggite Elizabeth (2020)
It is well known that students learn in a different way, and as a consequence they need different kind of stimuli. Multisensory learning is the kind of learning in which an individual uses the senses to learn. It is also a method by which students’ senses are stimulated at the same time, so their body receives information through each sensory system. Students learn best if they are immersed in a learning space with visual, auditory and kinesthetic resources. When students use of their sight, hearing, movement, and touch senses, they are engaged in language learning, especially in reading. The present project is based on students of second grade General Basic Education at Unidad Educativa Particular Bilingüe “Santo Domingo de Guzmán”, who show lack of motivation to read, difficulties in understanding and using some basic expressions or in identifying concrete information found in everyday life. As a consequence, they seem to be discouraged to learn the English language, especially reading………….